Hemitriakis indroyonoi sp. nov., a new species of houndshark from Indonesia (Carcharhiniformes: Triakidae) - White, William T.; Compagno, Leonard J. V.; _, Dharmadi (Zootaxa, 2009)
A new species of the genus Hemitriakis Herre, 1923 (Family Triakidae, Order Carcharhiniformes), is described from off the islands of Bali and Lombok in eastern Indonesia. Hemitriakis indroyonoi is separable from the other congeners, H. abdita, H. complicofasciata, H. falcata, H. japanica and H. leucoperiptera, by a combination of vertebral counts, morphometric characters, and juvenile coloration. H. indroyonoi is most similar to H. falcata from northwestern Australia but differs in juvenile coloration, some meristic and morphological characters, size and cranial morphology. The new species is allopatric to other members of this genus.